Approved budget : 1987 fiscal year (Lagos, Nigeria. Government of the Federal Republic of Nigeria, 1987)
The 1987 national budget speech was given by Major-General Ibrahim Babangida, addressing problems and constraints which were identified in the 1986 budget, notably the dependence on the oil sector; high inflation and unemployment levels; the twin issues of low productivity in agriculture and low capacity utilisation in manufacturing; the overstretched economic and social infrastructure; the heavy burden of both external and internal debts and; the distorted patterns of both domestic consumption and production.
Includes appendices.
ne 10/08/2021
Loans
Keywords: Budget; Nigeria